An efficient privacy preserving data aggregation approach for mobile sensing. Issue 16 (7th July 2016) - Zhang, Lichen; Wang, Xiaoming; Lu, Junling; Li, Peng; Cai, Zhipeng
Abstract: The advances in sensing capabilities of smartphones give rise to a variety of mobile participatory sensing applications that collect users' personal data. Because of the existence of both sensitive, private personal data, and untrusted aggregator, serious privacy concerns on users arise. Currently, existing privacy preserving data collection methods either require bidirectional communications between an untrusted aggregator and mobile users in every aggregation period, or have high computation or communication overhead. To address these problems, we propose an efficient data aggregation approach by which an untrusted aggregator in mobile sensing can collect the statistics over the data contributed by multiple mobile users, while supporting privacy preservation of each user and data integrity verification. In this approach, information hiding and homomorphic encryption are applied to guarantee the data privacy of mobile users. In detail, a breadth‐first search tree is first constructed at the initial phase among the mobile users, and then the original datum of each user is perturbed among its neighbors in ciphertext space by using information hiding and homomorphic encryption. The evaluations of our approach show that our protocol requires lower communication and computation overhead and thus more feasible for the computation constrained mobile devices. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The advances in sensing capabilities of smartphones give rise to a variety of mobile participatory sensing applications. However, serious privacy concerns arise. In this paper, we propose an efficient data aggregation approach by which an untrusted aggregator in mobile sensing can collect the statistics over the data contributed by multiple mobile users while supporting privacy preservation and integrity verification. In this approach, information hiding and homomorphic encryption are applied to guarantee the data privacy of mobile users.